Toxigenic dinoflagellates and associated toxins in San Jorge Gulf, Argentina - Fabro Cerreia Fus, Elena Inés (2018)
The occurrence of harmful algal blooms (HABs) is a global problem, and particularly in San Jorge Gulf (SJG), Argentina, which supports important fisheries, HABs represent a risk to human health. We studied the diversity and distribution of toxigenic dinoflagellates in the SJG using toxin detection and quantification, and assessed the connections between cell densities, toxins, and oceanographic parameters. Phytoplankton net samples were taken for microscopic and liquid chromatography-tandem mass spectrometry (LC-MSMS) analyses during an expedition aboard R/V Coriolis II in February 2014. Solid phase adsorption toxin tracking (SPATT) devices were also deployed to determine the presence of dissolved lipophilic toxins in seawater. Toxigenic dinoflagellate species and associated toxins showed different distribution patterns in the north and the south SJG. Protoceratium reticulatum and Dinophysis acuminata, together with yessotoxin and pectenotoxins, were predominantly detected in the northern SJG, mainly associated with low-nutrient, warmer waters. By contrast, Alexandrium catenella and paralytic shellfish toxins showed the highest relative abundances in the southern SJG, associated with high-nutrient, low-temperature waters. Cellular toxin content was also differently affected by environmental parameters, highlighting the complexity of HABs in this area. Spirolides were detected by SPATT for the first time in the SJG, suggesting the occurrence of A. ostenfeldii.